Pembuatan Minuman Berbahan Dasar Bunga Krisantemum Dengan Penambahan Agar-Agar - Adawiyah, Robiatul; Fransisca, - (Jurnal Ilmiah Pariwisata, 2018)
Experimental research about adding gelatin in Chrysanthemum-based drinks, recipe made from Krisanthemum Flower which is the most favored by the people and how the level of people's preference for the Krisantemum Flower-based drink is the most favored by the community. The tests used in this experimental study were sensory tests or organoleptic tests which only used a distinctive and descriptive test as well as a hedonic test on 80 untrained panelists. This study has the results of a descriptive test in the organoleptic test in the form of a sample formulation of 080 which got the highest score of 2.96 in terms of taste and 3.90 in terms of aroma, and sample 894 received the highest score of 3.68 in terms of texture of Chrysanthemum Flower based drinks. Then for the results of the hedonic test or preference test obtained in the form of 191 samples most preferred by panelists with a value in terms of taste of 0.032, in terms of texture of 0.059 and in terms of aroma of 0.099.